Modeling the Enantioselective Enzymatic Reaction with Modified Genetic Docking Algorithm - Žiemys, A.; Rimkutė, L.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2004)
The handling algorithms for molecular interaction and docking is of increasing involvement in biological processes modeling. Genetic algorithm, in particular, improves the computation models and leads to more effective and robust calculations. An example of genetic algorithm application for the treatment of enantioselective enzymatic (peroxidase catalyzed) reaction is rendered. The performed modeling revealed the substrate structure influence to the docking in the enzyme active center and provided an explanation to the mechanism of peroxidase-catalyzed asymmetric oxidation reaction. The comparison of modeling results with published experimental data revealed the effectiveness of used algorithm, its suitability for solving problems for enantioselective enzymatic reactions modeling and its relevance to provide the rational design of fine prechiral compounds based targets.